Exploring the Potential of Vietnamese Traditional Medicinal Herbs: Trends, Challenges, and Global Market Opportunities - NGUYEN, Duy Duc (International Journal of Scientific Research and Management (IJSRM), 2024)
Traditional Vietnamese medicine (TVM) plays a significant role in healthcare, being deeply intertwined with cultural heritage and community practices. This research paper explores the potential of Vietnamese traditional medicinal herbs, focusing on consumer trends, challenges, and global market opportunities. This exploration highlights the intricate dynamics that influence the accessibility and sustainability of traditional remedies. Using a mixed-methods approach, a comprehensive literature review, and data analysis, this study examines the economic impact and market dynamics of traditional medicinal herbs from Vietnam, emphasizing their historical significance, contemporary relevance, and prospects. Key findings underscore the substantial growth potential and offer insights into how Vietnamese medicinal herbs can establish a more prominent presence in the global market